Medicolegal Approach to Post-Injection Neuropathy Cases - Ünal, Volkan; Ünal, Esra özgün; Emir, Abdurrahman; Özer, Yusuf; Çağdır, Sadi (The Bulletin of Legal Medicine, 2015)
Objective: Redundant injections, false administration techniques and the injections applied by unqualified personnel can cause injection neuropathy. The purpose of this study is to characterize the post-injection neuropathy cases, to identify the active ingredients used for injection and, knowing the fact that the a number of sciatic nerve injuries are secondary to medical intervention, to discuss if post-injection neuropathy can be considered as malpractice.Materials and methods: A retrospective study was conducted based on the analysis of 121 cases which were sent to the Council of Forensic Medicine from the courts with a post-injection neuropathy claim in 2008-2010. All patients were evaluated for the agent injected, indication for injection and person who injected the drug and the severity of neurodeficit.Results: It was found that 107 (88.4 %) of 121 cases sent to Council of Forensic medicine were male, 14 (11.6%) of them were female. Majority (n=93, %76.8) of the injections were applied by a nurse or health officer. Diclofenac sodium is the major injection agent. While 47 (38.8%) of the cases had only diclofenac sodium injection, with combined treatments 58 of the cases had diclofenac sodium injected. On the other hand, 10 (8.3%) of the cases were injected with analgesics, whose active ingredients couldn’t be determined from the medical records. In one case the doctor and the nurse was found responsible for the post-injection neuropathy.Conclusions: Animal testing shows that the injection neuropathy can happen because of the toxic effects of the injection agent. Even if the injection done properly, there may happen various neurological sequels, but being careful while choosing injection agent and educating medical staff should lower the rates of unwanted complications.Keywords: Injection Neuropathy, Intramuscular Injection, Malpractice
Keywords: injection neuropathy; intramuscular injection; malpractice